Konstruksi Pemberitaan Politik Ber-isu Gender - Wulandari, Diah (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2012)
AbstractMass media has become one of the essential elements in the distribution of information relating to women's rights and gender justice. Through publicity and coverage on various issues of women, mass media can influence the way readers view the perspective of women and gender sensitive or, even conversely, the more gender bias. This research was conducted with three objectives: (1) to determine her political news on gender issues such as what is included in the five themes of political news in Kompas, (2) to understand the dominant ideology of capitalist patriarchy in the construction of political news with gender issues in Kompas, and (3) to label capitalistic patriarchal ideology that is used by Kompas in constructing the political news with gender issues. The study shows that patriarchy ideology arises two framing concepts political masculinity and woman marginalization in political news.Â Keywords : politics, gender, mass media